2019
DOI: 10.1101/789768
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic dysregulation of the lysophospholipid/autotaxin axis in the chromosome 9p21 gene SNP rs10757274

Abstract: AbstractAimsCommon chromosome 9p21 SNPs increase coronary heart disease (CHD) risk, independent of “traditional lipid risk factors”. However, lipids comprise large numbers of structurally-related molecules not measured in traditional risk measurements, and many have inflammatory bioactivities. Here we applied lipidomic and genomic approaches to three model systems, to characterize lipid metabolic changes in common Chr9p21 SNPs which confer ∼30… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, the underlying mechanism for the involvement of rs10757274 in cardiovascular disease is still not clear [32]. Recent studies have shown that rs10757274 risk allele can cause metabolic dysregulation of the lysophospholipid/autotaxin axis and increase the risk of CAD, which may be helpful for the identification of novel CAD risk markers that are independent of TCRFs [38].…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanism for the involvement of rs10757274 in cardiovascular disease is still not clear [32]. Recent studies have shown that rs10757274 risk allele can cause metabolic dysregulation of the lysophospholipid/autotaxin axis and increase the risk of CAD, which may be helpful for the identification of novel CAD risk markers that are independent of TCRFs [38].…”
Section: Discussionmentioning
confidence: 99%
“…In individuals harboring the SNP rs10757274 on chromosome 9p21, which increases the risk for coronary heart disease by 30% independent of traditional risk factors, the activity of plasma ENPP2 was uncoupled from the production of LPAs. 37 Thus, the inversion of the ENPP2/LPA ratio in the circulation might be representative of increased atherogenesis due to enhanced production of LPAs at the vessel wall.…”
Section: Discussionmentioning
confidence: 99%
“…Cell pellets of 10 6 cells were stored at −80 °C until extraction. Following a protocol already described in the literature, 23 lipids were extracted by a two-step liquid−liquid extraction using 2-propanol-hexane followed by a modified Bligh and Dyer protocol. 27 Further information can be found in the Supporting Information.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…21,22 In lipidomics or metabolomics, the detection of differences between samples is important to discover the influence of environmental changes, genetic differences, or biological markers for a certain disease pattern. 23 Therefore, the quality of the detected features is important so that they can actually be assigned to substances contained in the samples and reliably detected across all samples. Often, high background noise leads to the detection of many "features" which do not have a clear connection to a measurable chemical signal which we refer to as false-positive features.…”
Section: ■ Introductionmentioning
confidence: 99%